2010
DOI: 10.1111/j.1755-0998.2010.02861.x
|View full text |Cite
|
Sign up to set email alerts
|

Strong correlation between cross‐amplification success and genetic distance across all members of ‘True Salamanders’ (Amphibia: Salamandridae) revealed by Salamandra salamandra‐specific microsatellite loci

Abstract: The unpredictable and low cross-amplification success of microsatellite loci tested for congeneric amphibian species has mainly been explained by the size and complexity of amphibian genomes, but also by taxonomy that is inconsistent with phylogenetic relationships among taxa. Here, we tested whether the cross-amplification success of nine new and 11 published microsatellite loci cloned for an amphibian source species, the fire salamander (Salamandra salamandra), correlated with the genetic distance across all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 36 publications
3
56
1
Order By: Relevance
“…[19]). Our results from the Indirana genus conform to these general patterns, and the observed cross-species amplification success rate of 11.3-29.0 % (mean = 21.2 %) is comparable to the within-genus amplification success rate of approximately 21 % reported for Ranid frogs [20].…”
Section: Discussionmentioning
confidence: 99%
“…[19]). Our results from the Indirana genus conform to these general patterns, and the observed cross-species amplification success rate of 11.3-29.0 % (mean = 21.2 %) is comparable to the within-genus amplification success rate of approximately 21 % reported for Ranid frogs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Sequence conservation of the flanking regions of microsatellite loci allowed primer pairs designed for one species to be shared with closely related taxa [49,50]. Among the Bovidae species, cross-species amplification of microsatellite primer pairs of Bos taurus showed 30 percent success rate in Capra hircus [51] and 40 percent in Ovis aries [49].…”
Section: Resultsmentioning
confidence: 99%
“…Studies in amphibians showed that the success of interspecific amplification was greatly variable, correlating with genetic distances between species. Moreover, it was phylogenetic divergence rather than the taxonomic position of the species that was the main criterion of successful interspecific amplification [78]. The review of the population structure of salmonids will continue and will also be focused on undergraduate and gradu ate students of different specialities.…”
Section: Discussionmentioning
confidence: 99%